Fuzzy multi objective optimization: With reference to multi objective transportation problem - Khan, A J; Das, D K (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> In this paper we present a review of the connection between modern era techniques & fuzzy multi objective optimization (FMOO) to deal with its shortcoming and FMOO used in transportation problem. Multi objective optimization represents an interest area of research since most real life problem have a set of conflict objectives. MOO has its root in late nineteenth century welfare economics, in the works of Edge worth & Pareto. But due to some shortcoming faces, researchers attract to FMOO and they use modern era technique like artificial intelligence. Finally we develop a fuzzy linear programming method for solving the transportation problem with fuzzy goals, available supply & forecast demand and showing a frame for fuzzy multi objective transportation problem (FMOTP) solution. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>